A proposed model for Process Mining Adoption - Berthold, Maike (2021)
Berthold, M., Cruz-Jesus, F., & Oliveira, T. (2021). A proposed model for Process Mining Adoption: Using a Mixed-Methods Approach. In APSI 2021 Proceedings: 21.ª Conferência da Associação Portuguesa de Sistemas de Informação (CAPSI’2021) 13 a 16 de outubro de 2021, Vila Real e Viseu, Portugal (pp. 1-14). Associação Portuguesa de Sistemas de Informação. https://aisel.aisnet.org/capsi2021/30